Macroeconomic Resilience in the Caribbean : 360° Resilience Background Paper - Li, Ran (World Bank, Washington, DC, 2021)
Macroeconomic shocks refer to any unpredicted disturbance to the economy through internal or external factors. Economic resilience is broadly defined as the inherent or policy-induced ability of individuals or communities to withstand or recover from the effects of the various shocks. The external shocks lead to volatilities and impose high risks on the economies. This chapter aims to characterize the overall macroeconomic resilience in the Caribbean region against a broad range of external shocks.